Home Security Monitoring System Based On Smartphone Application - Fitriyana Adila Md. Salleh; Aimi Syamimi Ab Ghafar (Progress in Engineering Application and Technology, 2024)
The rapid advancement of technology has transformed the traditional concept of home security systems. In the modern era, these systems now incorporate innovative solutions, utilizing applications on smartphones and connected devices. The proposed system seamlessly combines the power of smartphones with the versatility of ESP8266 to establish an efficient and cost-effective home security solution. Motion detectors serve as sensors to detect illegal intrusions, linked to the ESP8266 microcontroller, which acts as the central processing unit. This microcontroller processes data from sensors and transmits it to the smartphone application via Wi-Fi. For online connectivity, Blynk is employed before data is sent to smartphone applications, serving as a monitoring dashboard. Node red is essential for data processing, ensuring real-time connection between hardware and smartphone applications. This integration enables real-time monitoring and timely notifications through a user-friendly interface. The development environment for MIT Application offers powerful tools, including a visual layout editor, code editor, and debugging capabilities, streamlining the creation of feature-rich, user-friendly smartphone applications. The smartphone app serves as the user interface, allowing homeowners to access the security system in real time, receiving instant notifications and alerts upon detecting a security breach.